PENGARUH PENGGUNAAN BERBAGAI LEVEL KONSENTRAT MENGANDUNG ZnSO4 dan Zn-Cu ISOLEUSINAT TERHADAP PENGGUNAAN ENERGI KAMBING KACANG YANG MENGKONSUMSI SILASE SORGHUM–Clitoria ternatea (The effect of different level of concentrate additioncontaining ZnSo4.... - Norbertus Bria; Erna Hartati; Markus M. Kleden (Universitas Nusa Cendana, 2021)
The aim of this research was to measure the effect of different level of concentrate addition containing znso4 and zn-cu isoleusinat on energy utilization of kacang goats fed mixed silage of sorghum-clitoria ternatea. Twelve male kacang goats with average body weight 14.4 kg and 14.93 % coefficient of variation was used in this research. Experiment methode was used with research design was block randomised design consist of 4 treatments and 3 replications. The treatments were: T1: mixed silage of sorghum-Clitoriaternatea without concentgrate; T2; T3 and T4 was mixed silage of sorghum-Clitoriaternatea added by 10, 20 and 30 % of concentrate containg of 150 mg ZnSO4 and 2 % of Zn-Cu isoleusinat respectively. Parameter measured was consumnption and digestibility of anergy and blood glucose concentration. The result showed that addition of different level of concentrate containing ZnSO4 and Zn-Cu isoleusinatfollowed by increase of consumption and digestibility of energy and blood glucose concentration. It can be concluded the amount of concentrate providing containing of ZnSO4 and Zn-Cu isoleusinathad effect on energy consumption while no effect on digestibility of energy and blood glucose concentration. Further more 20 % of concentrate containg of ZnSO4 and Zn-Cu isoleusinat was the greatest level.